2010
DOI: 10.1177/1756285609359317
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options in trigeminal neuralgia

Abstract: The incidence of trigeminal neuralgia (TN) is 4.3 per 100,000 persons per year, with a slightly higher incidence for women (5.9/100,000) compared with men (3.4/100,000). There is a lack of certainty regarding the aetiology and pathophysiology of TN. The treatment of TN can be very challenging despite the numerous options patients and physicians can choose from. This multitude of treatment options poses the question as to which treatment fits which patient best. The preferred medical treatment for TN consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
138
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 59 publications
5
138
0
1
Order By: Relevance
“…Previous studies report pain free rates during first year after RF between 68-85% [13,14]. Kanpolat et al [15], finds a recurrence rate of 7.7% in the first 6 months after RF and 17.4% later on.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report pain free rates during first year after RF between 68-85% [13,14]. Kanpolat et al [15], finds a recurrence rate of 7.7% in the first 6 months after RF and 17.4% later on.…”
Section: Discussionmentioning
confidence: 99%
“…Oxcarbazepine a prodrug of carbamazepine has been shown to have equal efficacy but with less side effects and better tolerance (18,23,30,39). In a review of 3 RCTs it was found that reduction in attacks were similar with CBZ and oxcarbazepine (40).…”
Section: • Depressionmentioning
confidence: 99%
“…Carbamazepine is the is the first line drug in the management of TN. Several studies and systematic reviews have shown that this is the most effective drug in trigeminal neuralgia.It is considered the gold standard drug in treatment of symptoms of Trigeminal neuralgia (8,16,18,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The advised dosage is 200-1200 mg/day according to the current evidence based guidelines (18,21).…”
Section: • Depressionmentioning
confidence: 99%
“…Common side effects of the aforementioned surgical options include sensory loss (50%), dysesthesias (6%), anesthesia dolorosa (4%), and corneal numbness (4%). 11,22,30 Another, often more favorable, nondestructive surgical option is microvascular decompression (MVD). This procedure often leads to very good, sustained pain relief and is highly recommended for younger patients or those with few to no comorbidities.…”
mentioning
confidence: 99%
“…Destructive procedures include rhizotomy, balloon compression, and radiofrequency thermocoagulation. 22 Rhizotomy involves injecting an agent directly into the affected nerve branch. In balloon compression a small balloon can be inserted into the nerve branches to compress the nerve within a bony foramen.…”
mentioning
confidence: 99%